Respiratory Viruses in Pediatric Patients with Suspected COVID-19 at the Early Stages of the Pandemic: A Single-center Experience - Neslihan Zengin; Alkan Bal; Sinem Atik; Semra Şen Bayturan; Sinem Akçalı (Journal of Behçet Uz Children's Hospital, 2022)
Objective: This study aimed to report the respiratory tract viruses we detected in the respiratory polymerase chain reaction (PCR) samples taken from patients admitted to the Pediatric Emergency Service with suspicion of coronavirus disease-2019 (COVID-19) in the early stages of the pandemic, in addition to the clinical course, and laboratory features of the disease caused by these identified respiratory tract viruses. Method: All upper respiratory tract PCR samples were taken simultaneously from patients suspected of having COVID-19 disease. All pediatric patients who came to the Pediatric Emergency Department with suspicion of COVID-19 disease between March and June 2020 were included in the study. We retrospectively compared the laboratory findings, clinical manifestations, and primary outcomes of the children aged between 1 month and 18 years infected with respiratory viruses (RVs) and severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) virus. Results: Fifty-eight pediatric patients were tested. SARS-CoV-2 virus was detected in 27 (46.6%) patients and other RVs in 31 (53.4%) patients. The detection rate of SARS-CoV-2 was significantly higher in the older age group of children (p<0.01). We didn't detect co-infections with SARS-CoV-2 and other RVs in these patients. Compared to the children with COVID-19, those infected with other RVs required markedly higher rates of oxygen supplementation (p<0.01). There was no need for hospitalization in the COVID-19 patient group, and 23 of 31 critically ill children infected with other RVs were followed up in the pediatric intensive care unit. Conclusion: RVs are common causes of childhood infections and may cause critical illness. Infections caused by other RVs progressed with more severe clinical findings than those of COVID-19 disease in pediatric patients. During the COVID-19 pandemic, other RVs that cause mortality and morbidity in children should be also kept in mind.